Pembatalan Vonis Nihil Terhadap Terpidana yang telah dipidana Penjara Maksimum yang Melakukan Kembali Tindak Pidana dihubungkan dengan Putusan Mahkamah Agung Nomor 1354k/ Pid/2022 - Saepudin, Asep Sanda; Indarsih, Yuli (Universitas Pahlawan Tuanku Tambusai, 2024)
This research is connect to the cancellation of a zero verdict against a defendant who has been sentenced to a maximum of 20 years based on Supreme Court Decision Number 1354K/Pid/2022. The purpose of this research is to understand and explain how the law is applied in imposing a zero verdict on a convicts who has been sentenced to a maximum prison term who re-commit a crime and efforts to achieve synchronization between the Criminal Code and the Criminal Procedure Code regarding the regulation of a zero verdict in relation to Supreme Court Decision Number 1354 K/Pid/2022. The research method used in writing is normative legal research, which is carried out by researching, investigating and reviewing sources that mainly come from library reference materials or secondary materials consisting of primary legal materials, secondary legal materials, and tertiary legal materials with a normative legal research approach method. The research results show that the application of the law in the Supreme Court Decision Number 1354K/Pid/2022 is correct and proper, because the crime committed is not categorized as concursus so that the concursus sentencing system cannot be applied and for reasons of justice and legal certainty. In addition, the Supreme Court Decision expands the application of the decision of Article 12 paragraph (4) of the Criminal Code which limits the maximum prison sentence to 20 years. Efforts to achieve synchronization between the Criminal Code and the Criminal Procedure Code regarding the regulation of a zero verdict are by revising Article 12 paragraph (4) of the Criminal Code (Article 68 paragraph (4) of Law No. 1 of 2024 concerning the Criminal Code or the new Criminal Code) and revising Article 1 number 11 of the Criminal Procedure Code and making new provisions in the Criminal Procedure Code that explicitly regulate a zero verdict along with its procedures and requirements.